REVIEW : POTENSI DAN ARAH PENGEMBANGAN AGROINDUSTRI BERBASIS KAKAO DI PROVINSI PAPUA BARAT - Murtiningrum Murtiningrum; Tajuddin Bantacut (Agroindustrial Technology, University of Trunojoyo Madura, 2016)
West Papua Province as the coverage area of the National Cocoa Revitalization Movement (GERNAS Pro-Cocoa). This area has the potential to become a center for the cocoa production, and even become the main cocoa producing areas in eastern Indonesia. Cocoa plantation area in West Papua province was recorded as 5.509 ha with 3.104 tons of total production. This article aims to provide an overview of cocoa as a national strategic competitive commodities and conditions of cocoa plantations in West Papua province. At the end of the text presented on the direction of cocoa develop agroindustry through institutional capacity building among farmers, groups of farmers, Farmers Group Association (gapoktan), traders, relevant institutions and universities. This paper also presented the opportunities and challenges of developing downstream cocoa industry in West Papua province. Cocoa agroindustry development in West Papua Province needs of reform to the institutional capacity building cocoa between farmers, groups of farmers, gapoktan, traders, wholesalers, relevant institutions and universities. This cooperation can create a new business strength, increasing market coverage, and quality assurance of products. Income of the cocoa farmer can be increased by developing a simple process cocoa processing using appropriate technology. The farmers can produce cocoa downstream products which have a higher economic value